Influence of integrated organic-inorganic Nitrogen on growth and nutrient concentration of summer Onion (Allium cepa (Bangladesh Journal of Agricultural Research, 2015)
An experiment was carried out to assess the effect of integrated organic and inorganic nitrogen on growth and nutrient concentration in summer onion (Allium cepa var. BARI Piaz-2). The study was done on a silty clay loam soil of Sher-e-Bangla Agricultural University Farm, Dhaka during kharif (March to October) season. The soil of the experimental site belongs to the Tejgaon series of AEZ No. 28, Madhupur Tract, classified as Shallow Red Brown Terrace Soils in Bangladesh soil classification system. Twelve treatments were used in the experiment and in each treatment, different combinations of urea, cowdung, and vermicompost were used to supply nitrogen (N) at the rate of 120 kg/ha. The treatments were arranged in a RCBD with three replications included- control or no fertilizer supplied (T1), 120 kg N/ha supplied from urea (T2), 100 kg N/ha supplied from urea with 20 kg from cowdung (T3), 100 kg N/ha supplied from urea with 20 kg from vermicompost (T4), 80 kg N/ha supplied from urea with 40 kg from cowdung (T5), 80 kg N/ha supplied from urea with 40 kg from vermicompost (T6), 60 kg N/ha supplied from urea with 60 kg from cowdung (T7), 60 kg N/ha supplied from urea with 60 kg from vermicompost (T8), 40 kg N/ha supplied from urea with 80 kg from cowdung (T9), 40 kg N/ha supplied from urea with 80 kg from vermicompost (T10), 120 kg N/ha supplied from cowdung (T11), 120 kg N/ha supplied from vermicompost (T12). Data on plant height, number of leaves, leaf length, bulb length, and bulb weight of onion were recorded. Samples of bulb and leaf were analyzed for determining the total nitrogen, phosphorous, potassium, and sulphur content. Height of plant ranged from 24.25 to 39.25 cm with lowest and highest value from T1 and T5, respectively. Like plant height, the longest leaf length (34.35 cm) and bulb length (2.79 cm) was observed in T5, whereas the shortest leaf length (21.20 cm) and bulb length (2.40 cm) was recorded in T1 treatment. Similarly treatment T5 showed the highest value for both bulb weight (30.40 g) and bulb yield (12.16 t/ha), whereas the lowest bulb weight (14.90 g) and bulb yield (5.96 t/ha) was obtained from T1 treatment. Statistically insignificant variations were recorded on number of leaves/plant. The highest nitrogen, phosphorous, potassium and sulphur content in bulb (2.30, 0.185, 1.71 and 0.96%, respectively) and in leaf (2.91, 0.183, 2.45, and 0.98%, respectively) were recorded in treatment T5. Whereas, the lowest nitrogen, phosphorous, potassium, and sulphur content in bulb (1.41, 0.055, 0.89, and 0.66%, respectively) and in leaf (2.15, 0.053, 1.71 and 0.63%, respectively) was found in T1. Therefore, the overall results suggest that treatment T5 which supplied 40 kg N/ha from cowdung and rest 80 kg from inorganic urea resulted in maximum plant growth and nutrient concentration and can be recommended for optimum production of summer onion DOI: http://dx.doi.org/10.3329/bjar.v39i3.21995 Bangladesh J. Agril. Res. 39(3): 529-545, September 2014